The Unknown Socrates - Rossetti, Livio (Peitho. Examina Antiqua, 2010)
The first part of the present paper argues against any attempts to find a set of fixed points of a doctrine that could be ascribed to Socrates. The main thesis of the article has it that Socrates was part of a cultural movement that was marked by a tendency to rather raise questions than merely provide answers and boast about having a number of doctrines or doxai of their own. The second part of the paper concentrates on a number of memorable innovations that eventually constituted Greek culture, e.g., the idea that it is possible and desirable to be in full control of oneself and, consequently, to shoulder responsibility for one’s deeds rather than merely avoid and deny it. Thus, Socrates and ancient Socratic literature are shown here to be a probable source of numerous ideas that the western civilization has built on for centuries, these being, for instance, the idea of the limits of our powers. Hence, the conclusion of the article is that it would be a serious mistake to exclude Socrates from this major cultural development, even though the thinker did produce neither a theory nor a body of theories.